Biallelic Mutations in DNM1L are Associated with a Slowly Progressive Infantile Encephalopathy. Issue 9 (11th July 2016) - Nasca, Alessia; Legati, Andrea; Baruffini, Enrico; Nolli, Cecilia; Moroni, Isabella; Ardissone, Anna; Goffrini, Paola; Ghezzi, Daniele
Abstract : Novel DNM1L mutations associated with impaired mitochondrial and peroxisomal morphology ABSTRACT: Mitochondria are highly dynamic organelles, undergoing continuous fission and fusion, and mitochondrial dynamics is important for several cellular functions. DNM1L is the most important mediator of mitochondrial fission, with a role also in peroxisome division. Few reports of patients with genetic defects in DNM1L have been published, most of them describing de novo dominant mutations. We identified compound heterozygous DNM1L variants in two brothers presenting with an infantile slowly progressive neurological impairment. One variant was a frame‐shift mutation, the other was a missense change, the pathogenicity of which was validated in a yeast model. Fluorescence microscopy revealed abnormally elongated mitochondria and aberrant peroxisomes in mutant fibroblasts, indicating impaired fission of these organelles. In conclusion, we described a recessive disease caused by DNM1L mutations, with a clinical phenotype resembling mitochondrial disorders but without any biochemical features typical of these syndromes (lactic acidosis, respiratory chain complex deficiency) or indicating a peroxisomal disorder.